Effectiveness of Consumption Iron Tablets with Orange Juice to Increase Haemoglobin Levels in Pregnancy - Tupriliany Danefi; Hapi Apriasih (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Pregnant women have a risk of anemia. The incidence of anemia in first trimester of pregnancy is 20%, second trimester of 70% and third of 70%. More than ¾ pregnant women experience iron deficiency and more than 1/3 pregnant women have anemia.The purpose of this research was to determine effectiveness of consumption iron tablets with orange juice to increase hemoglobin levels in pregnancy in the working area of Singaparna Public Health Center Tasikmalaya in 2019. Research used quantitative analytical with Quasi Experiment with design pre-test and post-test with control group. The analysis used is univariate, bivariate analysis used paired T- test and Wilcoxon test. The population in this research were all Trimester II pregnant women in Singaparna Public Health Center area with a sampling technique using purposive sampling to obtain a sample of 50 pregnant women. Based on the results of the research found that there was an increase in the average levels of Haemoglogin in the intervention group from 11.62% gr to 11.79 gr%, but these results were not statistically significant using the Wilcoxon test (P value 0.979). Control group (water) showed a decrease in haemoglobin levels from 11.68% gr to 11.38 gr% and this result was not statistically significant using the Paired T Test. The conclusion in this research is an increase in the average level of Hb in the intervention group (orange juice). Recommendations There is a need for control of diet which can also have an impact on increasing levels of Hb.